Effects of oxidation of lysozyme by hypohalous acids and haloamines on enzymatic activity and aggregation - Petronio, Maicon S.; Ximenes, Valdecir Farias [UNESP] (Elsevier B.V., 2012)
Hen egg white lysozyme (HEL), an antibacterial enzyme, is a prototype protein for studying the physical and chemical events that underlie the formation of amyloid fibril aggregates. Here, we studied alterations in enzymatic activity and aggregation provoked by oxidation of HEL by hypochlorous acid (HOCI), hypobromous acid (HOBr), taurine chloramine (Tau-NHCI), taurine monobromamine (Tau-NHBr), and taurine dibromamine (Tau-NBr2). Addition of only 4-fold molar excess of Tau-NHBr or Tau-NBr2 to HEL caused complete depletion of its intrinsic fluorescence, whereas HOCI and HOBr caused 40%-50% bleaching. Tau-NHCI was unable to oxidize lysozyme. The selective effect of bromamines on tryptophan residues had a direct effect on enzymatic activity: bromamines were about two-fold more effective as inhibitors of lysozyme than the acid precursors. The oxidation of HEL by HOCI and HOBr was more effective regarding the aggregation of the protein, which was evidenced by increased turbidity, Rayleigh scattering, and anisotropy. The aggregates presented spectroscopic properties that suggested the formation of amyloid fibrils, as measured by the thioflavin assay. In conclusion, the capacity of Tau-NHBr and Tau-NBr2 as inhibitors of the bactericidal activity of HEL could represent a role in the exacerbation of pulmonary infection, since leukocytes are rich sources of both taurine and HOBr. Moreover, the oxidation of HEL by just a small excess of hypohalous acids, a condition that could be found in inflammatory sites, may represent a new pathway for initiation of aggregation. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Amyloid fibril; Lysozyme activity; Hypobromous acid; Hypochlorous acid; Taurine monobromamine; Taurine dibromamine